2021
DOI: 10.1302/2633-1462.22.bjo-2020-0170.r1
|View full text |Cite
|
Sign up to set email alerts
|

Day-case total hip arthroplasty: a literature review and development of a hospital pathway

Abstract: Aims We present the development of a day-case total hip arthroplasty (THA) pathway in a UK National Health Service institution in conjunction with an extensive evidence-based summary of the interventions used to achieve successful day-case THA to which the protocol is founded upon. Methods We performed a prospective audit of day-case THA in our institution as we reinitiate our full capacity elective services. In parallel, we performed a review of the literature reporting complication or readmission rates at ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“… 20 Surrogates for elective surgery, such as the use of THA for hip fractures, also showcased the ability to provide arthroplasty services safely amid the COVID-19 pandemic. 21 A review and protocol by Haddad et al 22 identified several variables that were addressed to ensure that day surgery was feasible in the time of pandemic. These guidelines were also mirrored by the International Consensus Group of American Association of Hip and Knee Surgery (AAHKS).…”
Section: Discussionmentioning
confidence: 99%
“… 20 Surrogates for elective surgery, such as the use of THA for hip fractures, also showcased the ability to provide arthroplasty services safely amid the COVID-19 pandemic. 21 A review and protocol by Haddad et al 22 identified several variables that were addressed to ensure that day surgery was feasible in the time of pandemic. These guidelines were also mirrored by the International Consensus Group of American Association of Hip and Knee Surgery (AAHKS).…”
Section: Discussionmentioning
confidence: 99%
“…A host of preoperative, intraoperative, and postoperative strategies have been developed to minimize PBL 36 . Some centers have even used these strategies to define standard operating pathways for outpatient THA 4 . Recent studies have shown that the integrated use of these measures has resulted in a considerable decrease in PBL and transfusion rates following THA [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…As a prototype in PBM, TXA has reduced PBL by ;400 mL 38 . Despite these advances, no efforts should be spared to reduce PBL, which is of particular concern in patients undergoing outpatient THA, elderly patients, and patients with preoperative anemia 4,[40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations